Vitamin D supplementation improves anxiety but not depression symptoms in patients with vitamin D deficiency - Cuizhen Zhu; Yu Zhang; Ting Wang; Yezhe Lin; Jiakuai Yu; Qingrong Xia; Peng Zhu; Dao‐min Zhu (Brain and Behavior, 2020)
Abstract Objective Epidemiological evidence indicated a relationship between vitamin D (VD) and depression with anxiety, but their therapeutic relationship has not been fully elucidated. This study aimed to examine whether VD supplementation would relieve symptoms in patients with depression and anxiety with low serum 25‐hydroxy VD [25(OH) D] levels. Method Participants with low 25(OH)D levels were randomized to control or daily VD group and were followed up for 6 months. Serum concentrations of 25(OH) D were measured using commercial kits. Psychological symptoms were evaluated with the Hamilton Depression Rating Scale‐17 (HAMD‐17), Revised Social Anhedonia Scale (RSAS), Revised Physical Anhedonia scale (RPAS), and Hamilton Anxiety Rating Scale‐14 (HAMA‐14). The trial was listed in the trial registration (http://www.medresman.org.cn/uc/index.aspx; NTR number: ChiCTR2000030130). Results In this clinical population, no significant difference in depression symptoms was detected between VD group and control group at both baseline and at the endpoint of our study. The HAMD‐17, RSAS, and RPAS scores did not change significantly between VD and control groups from baseline to endpoint (all p > .05). However, there was a significant difference in time effect of the total HAMA‐14 scores between the two groups (β [95% Cl] = −2.235 [−3.818, −0.653], p = .006). Conclusions Vitamin D supplementation could improve the anxiety symptoms but not depressive symptoms in depressive patients with low VD level after the 6‐month intervention.